Implementation of Archipelago Dance as A Means of Introducing Cultural Literacy to Early Children - Wahyudi, Ayu Vinlandari (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2022)
Purpose – Nusantara dance contains local wisdom values that can be instilled early and impact individuals’ development, especially in early childhood. Early childhood tends to be more interested in modern dances. This study aims to explain the process of implementing Nusantara Dance to introduce cultural literacy in early childhood.Design/methods/approach – This research is qualitative with a field research approach. Data collection techniques in this study used observation, interviews, documentation, and literature studies based on relevant sources. Data analysis techniques were done through data reduction, presentation, and conclusion.Findings – The study results show that Nusantara Dance effectively introduces cultural literacy to early childhood, provides an understanding of cultural diversity in Indonesia, and knows the diversity of movement and music from every region in Indonesia. Research implications/limitations – Nusantara Dance is a medium to introduce cultural literacy to early childhood.Practical implications – This study implies that the stages in learning Nusantara Dance consist of appreciation, exploration, improvisation, and composing so that children can systematically understand the learning process.Originality/value – This study uses the Nusantara Dance media for early childhood, which aims to introduce cultural literacy to provide an understanding of Indonesia’s cultural diversity.Paper type: Research paper